Ambipolar Behavior of Ge-Intercalated Graphene: Interfacial Dynamics and Possible Applications - Zakharov, A. A. (Frontiers in Physics, 2021)
For the realization of graphene-based electronic and optic devices, the functionalization of this material becomes essential. Graphene doping through intercalation and tuning the chemical potential is one among other promising concepts. Intercalation of germanium is particularly interesting in view of its ambipolar doping behavior. Both p- and n-type doped graphene and their doping levels were identified by X-ray PhotoElectron Emission microscopy (XPEEM), Low Energy Electron Microscopy (LEEM) and Angle Resolved PhotoEmission micro-Spectroscopy (micro-ARPES). The absolute amount of intercalated Ge was determined to be roughly 1ML and 2MLs for n- and p-phase, correspondingly. For the samples in the present study we utilized the transition from 2ML to 1ML Ge via a mix phase after a high temperature annealing. Concrete implementation of mutual distribution of p- and n-phases depend on the temperature, mobility of Ge atoms in the second intercalated layer, cooling/heating protocol and can be nicely followed live in Low Energy Electron Microscope (LEEM) during heating/cooling below 5000C. The process has a significant temperature hysteresis which is an indication of the first order phase transition. The enhanced Ge diffusion in the second layer can be suitable for tailoring ultra-short junction lengths so that pseudo-spin mismatch can be used in future electronic concepts. Another application can utilize the negative relative refractive index at the p-n boundary and can find possible applications in focusing electron optics.